Bringing Local Wisdom into Mathematics: Developing a Culturally-Based Problem Posing Assessment - Ni Made Intan Kertiyani; Ulfa Lu'luilmaknun; Tabita Wahyu Triutami; Nourma Pramestie Wulandari; Maria Evelin Totuloba (FKIP Universitas Mataram, 2025)
This study aims to develop a local culture-based problem-posing test on linear programming material for eleventh-grade high school students and determine the content validity of the developed test based on expert judgment. The study employed a Research and Development (R&D) approach using the Four-D (4D) model. The developed test was designed to measure students’ abilities in three types of problem-posing activities: pre-solution posing, within-solution posing, and post-solution posing, by integrating local cultural contexts such as economic and agricultural activities around the Sembalun area of Mount Rinjani. The validation was conducted by two mathematics education experts and one local culture expert. The results showed that the developed test achieved a high level of content validity with an average score of 3.75, categorized as very valid. Therefore, the local culture-based problem-posing test developed in this study is considered feasible and valid to be used in assessing students’ abilities to formulate, develop, and solve contextual mathematical problems.